2006
DOI: 10.1177/0021998305056379
|View full text |Cite
|
Sign up to set email alerts
|

Gas Leakage Evaluation of CFRP Cross-ply Laminates under Biaxial Loadings

Abstract: In this study, leak characteristics of CFRP (carbon fiber reinforced plastic) cross-ply laminates are experimentally investigated under biaxial loadings using a specially prepared in-plane biaxial testing system. Permeability through the damaged laminate under biaxial stresses was measured with a leak detection system. In order to evaluate the effect of damage on leakage, ultrasonic C-scan was used to inspect the matrix cracking in the specimens. Experimental results reveal that leakage through the damaged lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
(19 reference statements)
1
16
0
Order By: Relevance
“…In previous study [13], biaxial load with load ratio 1:1 could not make matrix cracks in all layers in a carbon fiber/toughened epoxy laminate, which specimen configuration was identical with the specimen configuration in this paper, due to lower strain induced at the gauge area than biaxial load with other load ratio such as 1:0. However gauge area of the cruciform specimen was buckled under biaxial load with load ratio 1:0.…”
Section: Damage In Laminate Specimenssupporting
confidence: 64%
See 3 more Smart Citations
“…In previous study [13], biaxial load with load ratio 1:1 could not make matrix cracks in all layers in a carbon fiber/toughened epoxy laminate, which specimen configuration was identical with the specimen configuration in this paper, due to lower strain induced at the gauge area than biaxial load with other load ratio such as 1:0. However gauge area of the cruciform specimen was buckled under biaxial load with load ratio 1:0.…”
Section: Damage In Laminate Specimenssupporting
confidence: 64%
“…Generally, the permeation due to diffusion is much smaller than that due to leak through leakage paths. In our previous study [13], the effect of diffusion was confirmed to be negligible compared to leakage through cracks in the laminate. In this study, permeability through the laminate was presumed to be caused only by the leaks.…”
Section: Leakage Through Damaged Laminatesmentioning
confidence: 70%
See 2 more Smart Citations
“…Different lay-ups are tested in experiments such as cross-ply [2][3][4][5]8] and multi-directional ply composites [6][7][8], and textile composites [9]. Even though hydrogen is the working gas in the propellant tank, due to safety considerations, most researchers use helium gas instead in their experiments [2][3][4][5]8,9].…”
Section: Introductionmentioning
confidence: 99%